2018
DOI: 10.1007/s11701-018-0873-7
|View full text |Cite
|
Sign up to set email alerts
|

A matched and controlled longitudinal cohort study of dehydrated human amniotic membrane allograft sheet used as a wraparound nerve bundles in robotic-assisted laparoscopic radical prostatectomy: a puissant adjunct for enhanced potency outcomes

Abstract: We sought to explore the potency outcomes in two systematically controlled, non-randomized, matched, homogenous patient cohorts, which either underwent intervention (INT) with placement of dehydrated human amniotic membrane (dHAM) around nerve bundles (NVB) during robotic-assisted laparoscopic radical prostatectomy (RALP) or did not (CON). It is hypothesized that dHAM use would lead to better potency outcomes. 1400 eligible informed, consented patients underwent full bilateral nerve-sparing RALP by a single su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…13 A recent study reported the potency outcomes in 2 systematically controlled, non-randomized, matched, homogenous patient cohorts consisting of intervention with the placement of dehydrated human amniotic membrane around NVBs during radical prostatectomy or without (control). 14 The study concluded that the intervention with the placement of dehydrated human amniotic membrane was an independent significant (P < .001) predictor of achieving potency at 1 year and was 3.86 times (95% CI 2.43e6.13) more likely to achieve potency compared with the control. 14 Although this material has the potential to be a promising option for nerveregeneration in patients who underwent prostatectomy, we cannot ignore a limitation such as a supply problem associated with human resources.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…13 A recent study reported the potency outcomes in 2 systematically controlled, non-randomized, matched, homogenous patient cohorts consisting of intervention with the placement of dehydrated human amniotic membrane around NVBs during radical prostatectomy or without (control). 14 The study concluded that the intervention with the placement of dehydrated human amniotic membrane was an independent significant (P < .001) predictor of achieving potency at 1 year and was 3.86 times (95% CI 2.43e6.13) more likely to achieve potency compared with the control. 14 Although this material has the potential to be a promising option for nerveregeneration in patients who underwent prostatectomy, we cannot ignore a limitation such as a supply problem associated with human resources.…”
Section: Discussionmentioning
confidence: 94%
“…14 The study concluded that the intervention with the placement of dehydrated human amniotic membrane was an independent significant (P < .001) predictor of achieving potency at 1 year and was 3.86 times (95% CI 2.43e6.13) more likely to achieve potency compared with the control. 14 Although this material has the potential to be a promising option for nerveregeneration in patients who underwent prostatectomy, we cannot ignore a limitation such as a supply problem associated with human resources.…”
Section: Discussionmentioning
confidence: 94%
“…Mean time to continence was enhanced in HAM-group patients (1.21 months) versus (1.83 months; p = 0.033) and mean time to potency was 1.34 months versus 3.39 months; IIEF-5 score was higher in the HAM group 16.2 vs. 9.1. Another group matched 1400 patients undergoing full bilateral nerve-sparing robotic assisted RP by a single surgeon, wherein 700 patients had dHAM allograft wrapped around the NVB and 700 did not with retrospective follow-up of 1 year (IDEAL stage 2a) [40]. Groups were matched demographically, clinically, and biochemically.…”
Section: Discussionmentioning
confidence: 99%
“…Dehydrated human amnion/chorion membranes have been applied to cavernous nerves during RP as a source of implantable neurotrophic factors, growth factors, cytokines, proteases, and inhibitors of inflammatory and fibrotic pathways 125,135 . Limited human studies have applied these grafts during robotic-assisted RP with promising clinical outcomes of expedited recovery in erectile function 136,137 . The long-term efficacy, side effects and oncologic consequences of these grafts are unknown at this time and require future study.…”
Section: Amniotic Fluid Matricesmentioning
confidence: 99%